Implementasi Kurikulum 2013 dengan Authentic Assessment Pembelajaran Tematik di Sekolah Dasar - Khusnul Khotimah; Ade Mukhlis Supandi; Mohammad Agung Rokhimawan (SAP (Susunan Artikel Pendidikan), 2023)
The implementation of authentic assessment is carried out by the teacher without using proper assessment instruments. This study aims to describe the implementation of the 2013 curriculum authentic assessment in the thematic learning of class 1 Islamic elementary school. This research used qualitative methods with descriptive field research. The informants in the study were a teacher, students and student representative teacher. Data collection instruments were observation, interviews and documentation. Data analysis techniques were carried out using the Miles and Huberman models, then the validity of the data was tested using source triangulation. The results of the study illustrated that the implementation of the 2013 curriculum authentic assessment grade 1 has not been optimally implemented by teacher, because they often do not prepare instruments related to affective and psychomotor assessments. In the assessment of the affective part, the teacher only assesses students from their daily lives. In psychomotor assessment the teacher only assesses the results of student skills without making an assessment rubic.